Pull-in-voltage and RF analysis of MEMS based high performance capacitive shunt switch. (July 2018) - Pertin, Osor; Kurmendra,
Abstract: This paper presents design of a RF MEMS (Radio Frequency Micro Electro Mechanical system) capacitive shunt switch to study the switch performance which depends on various indices. To achieve high performance in the MEMS switch, the different component materials of the switch were chosen very carefully. Modeling equations were also derived for designed fixed-fixed beam of the switch considering formed capacitances in both upstate and downstate positions. The FEM simulation and accurate analytical results were obtained to study the effect of capacitance on the RF performance of the switch. The optimum dimensions were chosen for achieving a low pull in voltage as approximately 19 V for the designed switch. Static analysis confirms the optimum dimensions of the switch that provide several advantages such as high isolation, low insertion loss and low pull in voltage in the switch circuit. RF analysis study concludes that for the optimized switch provide return loss, insertion loss and isolation as −43 dB, −0.05 dB, −12 dB respectively.